Analisis Pengaruh Kelangkaan, Penyajian Produk, dan Motivasi Hedonis terhadap Pembelian Impulsif Secara Online pada Pengguna TikTok Shop Menggunakan Pendekatan Structural Equation Modeling (SEM) - syahwa, nurul mulya; Nafandra, Bunga; Putri, Olga Afrilly; Meilisa, Mira; Mukhti, Tessy Octavia (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
Impulsive online purchasing is a purchasing behavior that occurs spontaneously and unplanned during the online shopping process. Several factors that can influence impulsive online purchasing include scarcity, product presentation, and hedonistic motivation. The increase in impulsive online purchasing behavior cannot be separated from the digital marketing strategies intensively implemented by TikTok Shop. This research seeks to investigate the effects and relationship between scarcity, product presentation, and hedonistic motivation on online impulsive buying among TikTok Shop users. This study applies Structural Equation Modeling (SEM) as the analytical approach since it examines latent variables that are not directly observable, including scarcity, product presentation, and hedonic motivation. SEM is selected because it is capable of generating more robust and comprehensive results compared to simpler techniques such as multiple linear regression. The results demonstrate that scarcity, product presentation, and hedonic motivation significantly influence online impulse buying among TikTok Shop users, with hedonic motivation exerting a particularly strong effect on impulsive purchasing behavior. These three variables were found to contribute positively to impulsive buying behavior, with hedonistic motivation being the factor with the strongest influence. In the structural model, the coefficient values were 0.240 for scarcity, 0.250 for product presentation, and 0.331 for hedonistic motivation.